PERSEPSI GURU PAMONG TERHADAP KEMAMPUAN MENGAJAR MAHASISWA (Studi Kasus: SMKN 1 Tilatang Kamang dan SMKN 5 Padang) - 2113-2117, Insan Kamil (Universitas Negeri Padang, 2018)
Abstract-ThesuccessfulimplementationofPLKisdeterminedby manyfactors,one ofthemistheteachingabilityofPLKstudents.Thisresearchwasconductedtofind outtheperceptionofsupervisorteachersonteachingability ofPLKstudentsat SMKN 1 TilatangKamang and SMKN 5 Padang. The population of this descriptiveresearchwas all 34engineering teacherswhoactedassupervisor at both schools inacademicyear2016/2017.The researchsample was taken by usingtotalsamplingtechnique.Datawerecollectedby usingLikertscale questionnaires. The researchresultshowedthatthe perceptionofsupervisorteacherson teachingability ofPLKstudents was in fair category;for pedagogiccompetency was 74.93%orin faircategory; forpersonality competencywas74.87% orin faircategory;for social competencywas73.66% or infair category; andforprofessionalcompetencywas76.54% or also in faircategory. Key Word: perception, supervisor teacher, teaching ability